Descriptive Text Writing in the Perspective of Surface Strategy Taxonomy - Maharani, Mega Mulianing; Nugroho, Alfian Agung; Widiyati, Elok; Hidayati, Nani (Journal of Advanced Multidisciplinary Research, 2024)
The purpose of the study was to figure out the types of errors in the perspective of surface strategy taxonomy found in students’ descriptive writing. This study employed qualitative research. The population of the study was the tenth graders of SMA Islam Sultan Agung 1 Semarang. The sample of the study was 38 students of the tenth graders of X-IPS 1. They were given a descriptive text writing test. The result of the test were analyzed by using Surface Strategy Taxonomy. It classified the errors into four categories: omission, addition, misinformation, and misordering. The result of the study showed that the total errors were 91 errors. The errors consisted of omission with 38 errors (41.76%), misinformation with 33 errors (36.27%), addition with 14 errors (15.38%), and misordering with 6 errors (6.59%). From the data above, it can be concluded that omission was the most common error made by the students.